On Controls in Ancient Microbiome Studies, and Microbial Resilience in Ancient Samples - Santiago-Rodriguez, Tasha M. (Genes (Basel), 2018)
In the following comment, we reply to Eisenhofer and Weyrich’s letter “Proper authentication of ancient DNA is still essential” responding to the article “Gut Microbiome and Putative Resistome of Inca and Italian Nobility Mummies” by Santiago-Rodriguez et al. One of the concerns raised was the possibility that the patterns noted in the gut microbiome of pre-Inca/Inca and Italian nobility mummies were due to contamination of the blank control. When examining the blank controls and filtering the operational taxonomic units (OTUs) present in the blank controls, and further performing in-silico contamination analyses, we noticed very similar patterns as those previously reported. We also discuss controls in ancient microbiome studies, and aspects of microbial resilience in ancient samples.